Estimation of total phenolic and flavonoid content of Hibiscus furcatus Roxb leaves - Najuma Salim; Rahul Pratap; Abdul Vajid Komban; Surya Narayanan; Suma V.K (International Journal of Pharmacy and Analytical Research, 2022)
Hibiscus furcatus Roxb belonging to family, Malvaceae,is a herb ,used in traditional medicine for the treatment of inflammation, hyperdypsia, renal diseases etc. Ethanolic extract of Hibiscus furcatus was fractionated using different solvents of increasing polarity like petroleum ether, chloroform and ethylacetate. The preliminary phytochemical screening showed the presence of carbohydrates, steroids, flavonoids.